(ab+3)(ab−3)
=(ab+3)(ab+−3)
=(ab)(ab)+(ab)(−3)+(3)(ab)+(3)(−3)
=a^2b^2−3ab+3ab−9
=a^2b^2−9
Answer:
x^2 + 2x +1 = 2x + 2
Step-by-step explanation:
(x+1) = 2
multiplying both sides by x +1
(x +1) (x+1) = 2 (x+1)
x^2 + 2x +1 = 2x + 2
-9/2 = -1/4(-2)+ b
-9/2 = 1/2 + b
Minus 1/2 over
B= -5
Hope this helps!
Answer:
The square root of 45600 is 20![\sqrt{114}](https://tex.z-dn.net/?f=%5Csqrt%7B114%7D)
Step-by-step explanation:
One fraction that can be form is ![\frac{20\sqrt{x}}{1}](https://tex.z-dn.net/?f=%5Cfrac%7B20%5Csqrt%7Bx%7D%7D%7B1%7D)